THE USE OF QUIZIZZ APPLICATION IN IMPROVING STUDENTS’ READING COMPREHENSION SKILL AT SMKN 3 TAKALAR: An Experimental Research - Nanda , Siti Reski; Abdul, Nurdevi Bte; Daddi, Herlina (Journal of Computer Interaction in Education, 2018)
The researcher aimed at investigating the use of Quizizz Application in improving students’ reading comprehension skill. A Pre-Experimental desigm was employed only one classes of the tenth grades at one school and selected with total sampling as sample. The data were obtained through a pre-test, a post-test. The reading comprehension assessment was covering identifying main idea, identifying supporting details, identifying reference, understanding vocabulary, and making inference. The compulation showed that the used Quizizz Application was improving the students’ reading comprehension skills, students’ reading comprehension skill using the Quizizz Application show better learning outcomes than before the Quizizz Application was applied. The results of inferensial statistical analysis using the t test formula, it is known that the value of t calculations obtained are 6.25 with frequency db = 25-1 = 24, at the 50% significance level obtained t-table = 2.064. So, t-count> t table or null hypothesis (HO) is rejected and the alternative hypothesis (H1) is accepted. The use of Quizizz Application was very enjoyble in the learning process and it could help that designing the learning purpose appropriately considers language level may ease teacher to use the Quizizz Application in improving students’ reading comprehension skill